Cognitive Bias And Decision-Making Quality In Contemporary Accouting Practice : A Systematic Review Of The Literature - Ralfsamy, Achmad Daffa; Agustin, Devina; Aprilianz, Flowrent; Rizkiyah, Miftahul; Yusnaini, Yusnaini (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study systematically reviews the literature on cognitive bias and its influence on the quality of professional judgment in contemporary financial reporting practices. The review focuses on key areas of financial reporting judgment, including accounting estimates, accounting policy choices, and disclosure and materiality assessments. Using a Systematic Literature Review approach, this study analyzes 37 empirical articles published between 2020 and 2026 to synthesize evidence on behavioral influences in financial reporting contexts. The findings indicate that prior research predominantly concentrates on accounting estimates such as impairment, fair value measurement, provisions, and allowance estimation due to their inherent uncertainty and reliance on managerial discretion. Experimental research designs dominate the literature, reflecting a strong emphasis on individual level behavioral analysis, while survey and archival approaches remain comparatively limited. Across studies, anchoring bias, confirmation bias, overconfidence, and availability bias emerge as the most consistently identified cognitive distortions affecting financial reporting judgment, particularly under conditions of high estimation uncertainty, time pressure, and information complexity. This review highlights the growing relevance of behavioral perspectives in financial reporting research and underscores the importance of debiasing mechanisms and professional skepticism in enhancing judgment quality and reducing systematic decision making errors. The study contributes by providing an integrated synthesis of recent evidence and identifying directions for future research on behavioral influences in accounting practice